Improving the Electrochemical Performance of Lithium Metal Batteries with Hollow Shell Microspheres and Polypyrrole Vapor Phase-Coated LiV3O8 Cathodes. Issue 13 (13th September 2018) - Bae, Ki Yoon; Park, Gi Dae; Kim, Byung Hyuk; Cho, Sung Ho; Kang, Yun Chan; Lee, Kyoung Don; Yoon, Woo Young
Abstract : New hollow shell structured lithium trivanadate (LiV3 O8 ) microspheres were synthesized by a spray drying method, and the effect of a vapor-phase-polypyrrole coating on the surface of this active material was studied. A thin and uniform coating layer could form by a simple vapor-phase-polymerization (VPP) method. The polypyrrole coating layer not only compensates for the low conductivity of the active material but also prevents its direct contact with the electrolyte and reduces vanadium dissolution. The LiV3 O8 morphology and presence of the coating layer were confirmed using Fourier-transform infrared spectroscopy, field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, and transmission electron microscopy. The electrochemical performance was analyzed using a battery testing system and impedance spectroscopy. The cycle performance of the Li-powder/polypyrrole-VPP-coated hollow shell LiV3 O8 cell showed a higher capacity and greater capacity retention (LiV3 O8 : 160.80 mA h g −1, 62.31%; coated LiV3 O8 : 206.55 mA h g −1, 82.02%) in the range of 1.8–4.0 V at a 0.2 C-rate, even after 200 cycles. The rate capability at various current densities was also high. Further, it had a low charge transfer resistance, which remained low even after many cycles. Thus, the combined effect of hollow-shell-structure and polypyrrole-VPP coating, led LiV3 O8 to its improved electrochemical performance.